TPACK in Action Berbasis Canva: Transformasi Pembelajaran Bangun Datar untuk Menajamkan Pemahaman dan Keterampilan Komunikasi Siswa - Ramzil Huda Zarista; Mimi Hariyani; Dessy Syofiyanti; Emy Yunita Rahma Pratiwi; Silvia Anggri Wijaya; Dian Purnomo (Prodi Pendidikan Guru Sekolah Dasar, 2026)
This research is motivated by the low understanding of the concept of flat building and mathematical communication skills of elementary school students which are still abstract and have not been supported by innovative and technology-based learning tools. The integration of the Technological Pedagogical Content Knowledge (TPACK) framework with the use of Canva's digital media is a solution to create more visual, interactive, and meaningful learning. This research aims to develop a Canva-based teaching module that is integrated with TPACK and test its validity, practicality, and effectiveness in improving students' understanding of mathematical concepts and communication skills. The method used is Research and Development (R&D) with a 4D model which includes the define, design, develop, and disseminate stages. The product developed is a Canva-based digital teaching module designed by systematically integrating content, pedagogy, and technology aspects. The research subjects were elementary school grade V students involving validators who were experts in material, media, and language. The research instruments include validation sheets, teacher and student response questionnaires, concept comprehension tests, and mathematical communication skills tests. The results of the study show that the teaching modules developed are in the category of being very valid, practical, and effective in improving student learning outcomes. This is shown by a significant improvement in students' understanding of concepts and mathematical communication skills based on N- Gain analysis with medium to high categories. These findings indicate that Canva-based teaching modules within the TPACK framework are able to transform flat-wake learning to be more engaging, contextual, and student-centered.